Whaling, agreement between the United States of America and Iceland, effected by exchange of letters signed at Washington September 14 and 15, 1987. - Iceland.; United States. 1987 Sept. 14. Treaties, etc. Iceland.; United States. Department of State. (Washington, D.C. : Dept. of State : For sale by the Supt. of Docs., U.S. G.P.O., 1993)
Mode of access: Internet.